Water-based varnish suitable for photovoltaic glass glaze as well as preparation method and application of water-based varnish

By using aqueous ink mixing oil composed of aqueous alcohol ether solvent, aqueous polyurethane dispersion and oxazolin-based water-soluble acrylic polymer, the problem of high temperature and long-term curing treatment of existing photovoltaic glass glaze ink mixing oil is solved, and the problem of high temperature and long time of curing treatment of existing photovoltaic glass glaze is achieved. The crosslinked structural coating with short-term curing at low temperature has excellent adhesion and impact resistance.

CN119432153APending Publication Date: 2025-02-14WUJIANG CSG GLASS CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411369092.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The ink-adjustment oil of existing photovoltaic glass glaze requires high temperature and long time during curing, resulting in the cured coating being flexible before tempering and easily forming defects such as pits and cracks.

Method used

The aqueous ink oil composed of aqueous alcohol ether solvent, aqueous polyurethane dispersion and oxazolin-based water-soluble acrylic polymer was prepared by low-temperature and short-term curing treatment (100-120℃, 30-40S) layer.

Benefits of technology

The cured coating is rigid and non-stick before tempering, avoiding defects such as pits and cracks caused by external factors, and reducing production energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005069074280000071
    Figure BDA0005069074280000071
Patent Text Reader

Abstract

The invention discloses water-based varnish suitable for photovoltaic glass glaze, which is prepared from the following raw material components in parts by weight: 60 to 80 parts of water-based alcohol ether solvent, 20 to 40 parts of water-based polyurethane dispersion and 1 to 5 parts of oxazolinyl water-soluble acrylic polymer. According to the water-based varnish suitable for the photovoltaic glass glaze, the high-acid-value water-based polyurethane dispersoid is adopted, the oxazoline-based water-soluble polymer is used as a thermal cross-linking agent, and the photovoltaic glass glaze system is borne and coated on gaps of battery pieces on back plate glass during silk-screen printing; the curing coating with a cross-linked structure is prepared through low-temperature and short-time curing treatment (100-120 DEG C, 30-40 S), the production energy consumption is effectively reduced, the curing coating is rigid and non-sticky before tempering, and the defects of pits, cracks and the like caused by the fact that external factors make contact with the surface of the curing coating are effectively prevented.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photovoltaic glass, and in particular to an aqueous varnish suitable for photovoltaic glass glaze, a preparation method of the aqueous varnish and application of the aqueous varnish in photovoltaic glass glaze. Background Art

[0002] Double-glass photovoltaic modules are composed of front glass, back glass and solar cells, and are particularly suitable for relatively harsh climate environments, such as photovoltaic power stations in areas with high humidity. In order to effectively improve the power generation efficiency of double-glass photovoltaic modules, photovoltaic glass glaze can be applied to the gap between the cells on the back glass, thereby reflecting sunlight back to the cells for use.

[0003] Photovoltaic glass glaze is composed of glass powder, titanium dioxide, varnish, etc., among which polymer resin is used as adhesive in varnish. During silk-screen printing, the photovoltaic glass glaze system is coated on the gaps between the cells on the back glass, and then the whole is cured (180-220℃) to form a cured coating, and then the whole is tempered (600-720℃) to form a glaze layer.

[0004] The polymer resin used in the varnish in the prior art is a water-based acrylic resin. After curing treatment, water, alcohol ether solvents, etc. in the water-based acrylic resin are volatilized to form a film with adhesive properties.

[0005] However, the curing treatment of this type of varnish requires high temperature (180-220°C) and long time (40-60S), and the cured coating is flexible and sticky before tempering. External factors contact the surface of the cured coating to form defects such as pits and cracks. Summary of the invention

[0006] In order to overcome the defects of the prior art solutions, the object of the present invention is to provide an improved water-based varnish suitable for photovoltaic glass glaze.

[0007] The present invention adopts the following technical solutions:

[0008] A water-based varnish suitable for photovoltaic glass glaze comprises the following raw material components by weight: 60-80 parts of water-based alcohol ether solvent, 20-40 parts of water-based polyurethane dispersion, and 1-5 parts of oxazoline-based water-soluble acrylic polymer.

[0009] According to some preferred embodiments of the present invention, the aqueous polyurethane dispersion has an acid value of 30-35 mgKOH / g based on solid content.

[0010] Wherein, the acid value based on solid content (mgKOH / g) = (m 亲水扩链剂 / Mw 亲水扩链剂 )×56100 / (m 二异氰酸酯+m 催化剂 +m 聚己内酯二元醇 +m 聚己内酯三元醇 +m 亲水扩链剂 +m 成盐叔胺 +m 二胺扩链剂 ).

[0011] The acid value of the aqueous polyurethane dispersion based on the solid content is less than 30 mgKOH / g. The aqueous varnish prepared therefrom is used to make photovoltaic glass glaze, which needs to be cured at a higher temperature and for a longer time (130°C, 50S) to form a cured coating. After the impact test, there are pits but no cracks. The acid value of the aqueous polyurethane dispersion based on the solid content is greater than 35 mgKOH / g. The aqueous varnish prepared therefrom is used to make photovoltaic glass glaze, which has no pits or cracks after the impact test.

[0012] The aqueous polyurethane dispersion has an acid value of 30-35 mgKOH / g based on the solid content. The aqueous varnish prepared from it is used to make photovoltaic glass glaze, which can be cured at low temperature and in a short time (110°C, 35S) to form a cured coating with excellent adhesion and no pits or cracks after the impact test; the glaze layer made by tempering treatment also has excellent adhesion.

[0013] According to some preferred embodiments of the present invention, the molar number of oxazoline groups in the oxazoline-based water-soluble acrylic polymer is 80-120% of the molar number of carboxyl groups in the aqueous polyurethane dispersion.

[0014] The molar number of oxazoline groups is the percentage of the molar number of carboxyl groups in the aqueous polyurethane dispersion = (m 噁唑啉基水溶性丙烯酸聚合物 × oxazoline-based water-soluble acrylic polymer solid content × molar number of oxazoline groups based on solid content) / (m 水性聚氨酯分散体 × solid content of aqueous polyurethane dispersion × acid value based on solid content / 56.1) × 100%.

[0015] The solid content in the above formula is calculated by baking 1g of the sample at 120±2℃ for 2h, and calculating the percentage of the sample mass after baking to the sample mass before baking.

[0016] According to some preferred embodiments of the present invention, the oxazoline-based water-soluble acrylic polymer is selected from one or more of WS-300 (solid content 10%, 7.7 mmol / g oxazoline molar number based on solid content), WS-500 (solid content 39%, 4.5 mmol / g oxazoline molar number based on solid content) and WS-700 (solid content 25%, 4.5 mmol / g oxazoline molar number based on solid content) of Nippon Shokubai Co., Ltd.

[0017] According to some preferred embodiments of the present invention, the aqueous alcohol ether solvent is selected from one or more of diethylene glycol butyl ether, dipropylene glycol methyl ether and tripropylene glycol methyl ether.

[0018] According to some preferred embodiments of the present invention, the aqueous polyurethane dispersion includes the following raw material components, measured in parts by weight: 30-40 parts of a water-soluble solvent, 20-30 parts of a diisocyanate, 0.05-0.2 parts of a catalyst, 10-25 parts of a polycaprolactone diol, 5-15 parts of a polycaprolactone triol, 4-6 parts of a hydrophilic chain extender, 1-5 parts of a salt-forming tertiary amine, 5-8 parts of a diamine chain extender, and 100-150 parts of deionized water.

[0019] According to some preferred implementation aspects of the present invention, the water-soluble solvent is selected from one or more of N,N-dimethylformamide, N,N-diethylformamide, and N-methylpyrrolidone; the diisocyanate is selected from one or more of hexamethylene diisocyanate, isophorone diisocyanate, and 4,4-dicyclohexylmethane diisocyanate; the catalyst is selected from dibutyltin dilaurate (T-12); the polycaprolactone diol is selected from PCL-2102 (molecular weight Mn=1000g / mol) and PCL-2105 (molecular weight Mn=1000g / mol) of Juren Company. , PCL-2205 (molecular weight Mn = 2000g / mol) or more; polycaprolactone triol is selected from one or more of PCL-3057 (molecular weight Mn = 550g / mol), PCL-3087 (molecular weight Mn = 830g / mol), PCL-3207 (molecular weight Mn = 2000g / mol) of Juren Company; the hydrophilic chain extender is selected from anionic 2,2-dihydroxymethylpropionic acid; the salt-forming tertiary amine is selected from triethylamine; the diamine chain extender is selected from one or more of ethylenediamine, isophoronediamine, and 1,3-cyclohexanedimethylamine.

[0020] According to some preferred embodiments of the present invention, the aqueous varnish further comprises 1-5 parts of a rheological anti-settling agent and / or 1-5 parts of a dispersant, by weight.

[0021] According to some preferred implementation aspects of the present invention, the rheological anti-settling agent is selected from one or both of fumed silica and ethyl cellulose; the dispersant is an aqueous high molecular polymer, such as TEGO 755W from Evonik of Germany.

[0022] The present invention also provides a method for preparing the water-based varnish as described above, comprising the following steps:

[0023] The aqueous alcohol ether solvent, aqueous polyurethane dispersion, oxazoline-based water-soluble acrylic polymer and rheological anti-settling agent are mixed uniformly, heated to 80-90° C., cooled to 40-50° C. after the rheological anti-settling agent is completely dissolved, the dispersant is added into the system, mixed uniformly, and the aqueous varnish is obtained.

[0024] According to some preferred embodiments of the present invention, the aqueous polyurethane dispersion is prepared by the following method:

[0025] Mix the water-soluble solvent, diisocyanate and catalyst evenly, add polycaprolactone diol and polycaprolactone triol, slowly heat to 80-90°C and keep warm for 3-4h;

[0026] Cool down to 60-70℃, add hydrophilic chain extender, slowly heat to 80-90℃ and keep warm for 2-3h;

[0027] Cool down to 50-60°C, add salt-forming tertiary amine, neutralize for 1-1.5 hours, and obtain pre-watered polymer;

[0028] Adding a diamine chain extender into deionized water and mixing them evenly to obtain a diamine chain extender-deionized water solution;

[0029] Add a diamine chain extender-deionized water solution to the pre-watered polymer and emulsify for 40-60 minutes to obtain an aqueous polyurethane dispersion.

[0030] The present invention also provides a use of the above-mentioned water-based varnish in photovoltaic glass glaze.

[0031] The photovoltaic glass glaze comprises glass powder, titanium dioxide and water-based varnish, wherein the water-based varnish adopts water-based polyurethane dispersion as a binder and uses oxazoline-based water-soluble acrylic polymer as a thermal crosslinking agent. The photovoltaic glass glaze system is coated on the gaps between the cells on the back panel glass during screen printing and is cured to form a cross-linked structure cured coating.

[0032] Due to the adoption of the above-mentioned technical scheme, the present invention has the following advantages compared with the prior art: the water-based varnish suitable for photovoltaic glass glaze in the present invention adopts a high-acid value water-based polyurethane dispersion and an oxazoline-based water-soluble polymer as a thermal cross-linking agent. During silk-screen printing, the photovoltaic glass glaze system is coated on the gaps between the battery cells on the back glass, and is processed by low-temperature and short-time curing (100-120°C, 30-40S) to form a cross-linked structure cured coating, effectively reducing production energy consumption. The cured coating is rigid and non-sticky before tempering, effectively preventing external factors from contacting the surface of the cured coating to form defects such as pits and cracks. DETAILED DESCRIPTION

[0033] In order to enable those skilled in the art to better understand the technical solution of the present invention, the technical solution will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0034] The water-based varnish suitable for photovoltaic glass glaze of this embodiment includes the following raw material components by weight: 60-80 parts of water-based alcohol ether solvent, 20-40 parts of water-based polyurethane dispersion, and 1-5 parts of oxazoline-based water-soluble acrylic polymer.

[0035] The aqueous polyurethane dispersion has an acid value of 30-35 mgKOH / g based on solid content.

[0036] Wherein, the acid value based on solid content (mgKOH / g) = (m 亲水扩链剂 / Mw 亲水扩链剂 )×56100 / (m 二异氰酸酯 +m 催化剂 +m 聚己内酯二元醇 +m 聚己内酯三元醇 +m 亲水扩链剂 +m 成盐叔胺 +m 二胺扩链剂 ).

[0037] The molar number of oxazoline groups in the oxazoline-based water-soluble acrylic polymer is 80-120% of the molar number of carboxyl groups in the aqueous polyurethane dispersion.

[0038] The molar number of oxazoline groups is the percentage of the molar number of carboxyl groups in the aqueous polyurethane dispersion = (m 噁唑啉基水溶性丙烯酸聚合物 × oxazoline-based water-soluble acrylic polymer solid content × molar number of oxazoline groups based on solid content) / (m 水性聚氨酯分散体 × solid content of aqueous polyurethane dispersion × acid value based on solid content / 56.1) × 100%.

[0039] Wherein, the aqueous alcohol ether solvent is selected from one or more of diethylene glycol butyl ether, dipropylene glycol methyl ether and tripropylene glycol methyl ether.

[0040] Among them, the oxazoline-based water-soluble acrylic polymer is selected from one or more of WS-300 (solid content 10%, oxazoline molar number based on solid content 7.7 mmol / g), WS-500 (solid content 39%, oxazoline molar number based on solid content 4.5 mmol / g) and WS-700 (solid content 25%, oxazoline molar number based on solid content 4.5 mmol / g) of Nippon Shokubai Co., Ltd.

[0041] The aqueous polyurethane dispersion comprises the following raw material components by weight: 30-40 parts of water-soluble solvent, 20-30 parts of diisocyanate, 0.05-0.2 parts of catalyst, 10-25 parts of polycaprolactone diol, 5-15 parts of polycaprolactone triol, 4-6 parts of hydrophilic chain extender, 1-5 parts of salt-forming tertiary amine, 5-8 parts of diamine chain extender and 100-150 parts of deionized water.

[0042] The water-soluble solvent is selected from one or more of N,N-dimethylformamide, N,N-diethylformamide, and N-methylpyrrolidone; the diisocyanate is selected from one or more of hexamethylene diisocyanate, isophorone diisocyanate, and 4,4-dicyclohexylmethane diisocyanate; the catalyst is selected from dibutyltin dilaurate (T-12); the polycaprolactone diol is selected from PCL-2102 (molecular weight Mn=1000g / mol), PCL-2105 (molecular weight Mn=1000g / mol), and PCL-22 05 (molecular weight Mn = 2000g / mol) or more; polycaprolactone triol is selected from one or more of PCL-3057 (molecular weight Mn = 550g / mol), PCL-3087 (molecular weight Mn = 830g / mol), and PCL-3207 (molecular weight Mn = 2000g / mol) of Juren Company; the hydrophilic chain extender is selected from anionic 2,2-dihydroxymethylpropionic acid; the salt-forming tertiary amine is selected from triethylamine; the diamine chain extender is selected from one or more of ethylenediamine, isophoronediamine, and 1,3-cyclohexanedimethylamine.

[0043] In parts by weight, the aqueous varnish further comprises 1-5 parts of a rheological anti-settling agent and / or 1-5 parts of a dispersant.

[0044] The rheological anti-settling agent is one or two of fumed silica and ethyl cellulose; the dispersant is a water-based high molecular polymer, such as TEGO 755W from Evonik of Germany.

[0045] In this embodiment, a method for preparing the water-based varnish as described above comprises the following steps:

[0046] The aqueous alcohol ether solvent, aqueous polyurethane dispersion, oxazoline-based water-soluble acrylic polymer and rheological anti-settling agent are mixed uniformly, heated to 80-90° C., cooled to 40-50° C. after the rheological anti-settling agent is completely dissolved, the dispersant is added into the system, mixed uniformly, and the aqueous varnish is obtained.

[0047] Wherein, the aqueous polyurethane dispersion is prepared by the following method:

[0048] Mix the water-soluble solvent, diisocyanate and catalyst evenly, add polycaprolactone diol and polycaprolactone triol, slowly heat to 80-90°C and keep warm for 3-4h;

[0049] Cool down to 60-70℃, add hydrophilic chain extender, slowly heat to 80-90℃ and keep warm for 2-3h;

[0050] Cool down to 50-60°C, add salt-forming tertiary amine, neutralize for 1-1.5 hours, and obtain pre-watered polymer;

[0051] Adding a diamine chain extender into deionized water and mixing them evenly to obtain a diamine chain extender-deionized water solution;

[0052] Add a diamine chain extender-deionized water solution to the pre-watered polymer and emulsify for 40-60 minutes to obtain an aqueous polyurethane dispersion.

[0053] Example 1

[0054] The preparation method of the water-based varnish suitable for photovoltaic glass glaze in this embodiment comprises the following steps:

[0055] 1) Preparation of waterborne polyurethane dispersion

[0056] By weight, 38 parts of N,N-diethylformamide, 23 parts of 4,4′-dicyclohexylmethane diisocyanate and 0.1 parts of dibutyltin dilaurate (T-12) were mixed evenly, 12 parts of PCL-2105 (molecular weight Mn=1000 g / mol) and 13 parts of PCL-3087 (molecular weight Mn=830 g / mol) were added, and the temperature was slowly raised to 85°C and kept for reaction for 4 hours;

[0057] Cool down to 60°C, add 5 parts of 2,2′-dimethylolpropionic acid, slowly heat to 85°C and keep warm for 2 hours;

[0058] The mixture was cooled to 60°C, 4 parts of triethylamine were added, and the mixture was neutralized for 1 hour to obtain a pre-hydrated polymer;

[0059] Add 5 parts of 1,3-cyclohexanedimethylamine to 150 parts of deionized water and mix well to obtain a diamine chain extender-deionized water solution;

[0060] A diamine chain extender-deionized water solution was added to the pre-watered polymer and emulsified for 60 minutes to obtain an aqueous polyurethane dispersion.

[0061] The acid value of the aqueous polyurethane dispersion in this example is 33.73 mgKOH / g based on solid content.

[0062] 2) Preparation of water-based varnish:

[0063] 65.2 parts of dipropylene glycol methyl ether, 29.8 parts of aqueous polyurethane dispersion, 2 parts of WS-500 and 2 parts of ethyl cellulose were mixed evenly, and the temperature was raised to 80° C. After the ethyl cellulose was completely dissolved, the temperature was lowered to 50° C., 1 part of TEGO 755W was added to the system, and the mixture was mixed evenly to obtain the aqueous varnish.

[0064] The molar number of oxazoline groups in WS-500 in this example is 100% of the molar number of carboxyl groups in the aqueous polyurethane dispersion.

[0065] Example 2

[0066] The only difference between Example 2 and Example 1 is that the raw material component 2,2′-dimethylolpropionic acid in the aqueous polyurethane dispersion is 4.5 parts, the acid value of the aqueous polyurethane dispersion in this example based on solid content is 30.6 mgKOH / g, and the molar number of oxazoline groups in WS-500 is 107% of the molar number of carboxyl groups in the aqueous polyurethane dispersion.

[0067] Example 3

[0068] The only difference between Example 3 and Example 1 is that the raw material component WS-500 in the water-based varnish is 2.4 parts, and the molar number of oxazoline groups in WS-500 is 120% of the molar number of carboxyl groups in the water-based polyurethane dispersion.

[0069] Comparative Example 1

[0070] The only difference between Comparative Example 1 and Example 1 is that the raw material component 2,2′-dimethylolpropionic acid in the aqueous polyurethane dispersion is 3.5 parts, the acid value of the aqueous polyurethane dispersion in this example is 24.2 mgKOH / g based on solid content, and the molar number of oxazoline groups in WS-500 is 137% of the molar number of carboxyl groups in the aqueous polyurethane dispersion.

[0071] Comparative Example 2

[0072] The only difference between Comparative Example 2 and Example 1 is that the raw material component 2,2′-dimethylolpropionic acid in the aqueous polyurethane dispersion is 6.5 parts, the acid value of the aqueous polyurethane dispersion in this example based on solid content is 42.81 mgKOH / g, and the molar number of oxazoline groups in WS-500 is 78% of the molar number of carboxyl groups in the aqueous polyurethane dispersion.

[0073] Comparative Example 3

[0074] The difference between Comparative Example 3 and Example 1 is that the raw material component WS-500 in the water-based varnish is 1.4 parts, and the molar number of oxazoline groups in WS-500 is 70% of the molar number of carboxyl groups in the water-based polyurethane dispersion.

[0075] Comparative Example 4

[0076] The difference between Comparative Example 4 and Example 1 is that the raw material component WS-500 in the aqueous varnish is 2.8 parts, and the molar number of oxazoline groups in WS-500 is 140% of the molar number of carboxyl groups in the aqueous polyurethane dispersion.

[0077] Example 5

[0078] The preparation method of the photovoltaic glass glaze in this embodiment is as follows:

[0079] Put water-based varnish into a container and start stirring, put low-melting-point glass powder and titanium dioxide into the container in turn, and stir until they are uniform and free of lumps; put leveling agent and defoaming agent into the container in turn, and stir until they are uniform; then put them through three-roll milling to obtain photovoltaic glass glaze.

[0080] Tests and Results

[0081] The aqueous varnishes in Examples 1-3 and Comparative Examples 1-4 were made into photovoltaic glass glazes according to the preparation method in Example 5, and were silk-screened on the gaps between the cells on the back glass, and then the whole was cured to form a cured coating, and then the whole was tempered to form a glaze layer. The test results are shown in Table 1 below:

[0082] Table 1 Test results

[0083]

[0084] Table 1 related performance tests were conducted using the following methods:

[0085] Adhesion: Tested according to T / CPIA 0028.2-2021.

[0086] Impact resistance: The back glass with cured coating is placed horizontally, and a 227g (38.1mm diameter) steel ball is placed 50cm above the cured coating and allowed to fall freely. Observe whether there are pits or cracks at the landing point.

[0087] The results in Table 1 show that the photovoltaic glass glaze prepared by using the water-based varnish in Examples 1-3 of the present invention can be cured at low temperature and in a short time (110° C., 35 seconds) to prepare a cured coating, which has excellent adhesion and has no pits or cracks after the impact test; the glaze layer prepared by the tempering treatment also has excellent adhesion;

[0088] The water-based varnish in Comparative Example 1 was used to make photovoltaic glass glaze, which needed to be cured at a higher temperature and for a longer time (130° C., 50 seconds) to form a cured coating, which had pits but no cracks after the impact test;

[0089] The photovoltaic glass glaze made from the water-based varnish in Comparative Example 2 had no pits or cracks after the impact test;

[0090] The photovoltaic glass glaze made of the water-based varnish in Comparative Example 3 needs to be cured at a higher temperature and for a longer time (130°C, 50S) to form a cured coating, which has pits but no cracks after the impact test;

[0091] The photovoltaic glass glaze made from the water-based varnish in Comparative Example 4 had pits but no cracks after the impact test.

[0092] The water-based varnish suitable for photovoltaic glass glaze of the present invention adopts a high-acid-value water-based polyurethane dispersion and uses an oxazoline-based water-soluble polymer as a thermal crosslinking agent. During screen printing, the photovoltaic glass glaze system is coated on the gaps between the battery cells on the back plate glass, and is processed by low-temperature and short-time curing (100-120°C, 30-40S) to form a cross-linked structure cured coating, thereby effectively reducing production energy consumption. The cured coating is rigid and non-adhesive before tempering, and effectively prevents external factors from contacting the surface of the cured coating to form defects such as pits and cracks.

[0093] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the contents of the present invention and implement them accordingly. They cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A water-based varnish suitable for photovoltaic glass glaze, characterized in that: The raw material components are as follows: 60-80 parts of aqueous alcohol ether solvent, 20-40 parts of aqueous polyurethane dispersion, and 1-5 parts of oxazoline-based water-soluble acrylic polymer.

2. The aqueous varnish according to claim 1, characterized in that: The aqueous polyurethane dispersion has an acid value of 30-35 mgKOH / g based on solid content.

3. The aqueous varnish according to claim 1, characterized in that: The molar number of oxazoline groups in the oxazoline-based water-soluble acrylic polymer is 80-120% of the molar number of carboxyl groups in the aqueous polyurethane dispersion.

4. The aqueous varnish according to claim 1, characterized in that: The aqueous polyurethane dispersion comprises the following raw material components by weight: 30-40 parts of water-soluble solvent, 20-30 parts of diisocyanate, 0.05-0.2 parts of catalyst, 10-25 parts of polycaprolactone diol, 5-15 parts of polycaprolactone triol, 4-6 parts of hydrophilic chain extender, 1-5 parts of salt-forming tertiary amine, 5-8 parts of diamine chain extender and 100-150 parts of deionized water.

5. The aqueous varnish according to claim 4, characterized in that: The water-soluble solvent is selected from one or more of N,N-dimethylformamide, N,N-diethylformamide, and N-methylpyrrolidone; the diisocyanate is selected from one or more of hexamethylene diisocyanate, isophorone diisocyanate, and 4,4′-dicyclohexylmethane diisocyanate; the catalyst is dibutyltin dilaurate; the hydrophilic chain extender is anionic 2,2′-dihydroxymethylpropionic acid; the salt-forming tertiary amine is triethylamine; and the diamine chain extender is selected from one or more of ethylenediamine, isophoronediamine, and 1,3-cyclohexanedimethylamine.

6. The aqueous varnish according to claim 1, characterized in that: In parts by weight, the aqueous varnish further comprises 1-5 parts of a rheological anti-settling agent and / or 1-5 parts of a dispersant.

7. The aqueous varnish according to claim 6, characterized in that: The rheological anti-settling agent is selected from one or both of fumed silica and ethyl cellulose; and the dispersant is a water-based high molecular polymer.

8. A method for preparing the aqueous varnish according to any one of claims 1 to 7, characterized in that: The steps include: The aqueous alcohol ether solvent, aqueous polyurethane dispersion, oxazoline-based water-soluble acrylic polymer and rheological anti-settling agent are mixed uniformly, heated to 80-90° C., cooled to 40-50° C. after the rheological anti-settling agent is completely dissolved, the dispersant is added into the system, mixed uniformly, and the aqueous varnish is obtained.

9. The preparation method according to claim 8, characterized in that: The aqueous polyurethane dispersion is prepared by the following method: Mix the water-soluble solvent, diisocyanate and catalyst evenly, add polycaprolactone diol and polycaprolactone triol, slowly heat to 80-90°C and keep warm for 3-4h; Cool down to 60-70℃, add hydrophilic chain extender, slowly heat to 80-90℃ and keep warm for 2-3h; Cool down to 50-60°C, add salt-forming tertiary amine, neutralize for 1-1.5 hours, and obtain pre-watered polymer; Adding a diamine chain extender into deionized water and mixing them evenly to obtain a diamine chain extender-deionized water solution; Add a diamine chain extender-deionized water solution to the pre-watered polymer and emulsify for 40-60 minutes to obtain an aqueous polyurethane dispersion.

10. Use of the aqueous varnish according to any one of claims 1 to 7 in photovoltaic glass glaze.